The importance of domain-specific self-efficacy assessment for substance use and HIV care continuum outcomes among adults in an urban HIV clinic network. Issue 5 (4th May 2022) - Starks, Tyrel J.; Skeen, Simone J.; Jones, S. Scott; Millar, Brett M.; Gurung, Sitaji; Ferraris, Christopher; Ventuneac, Ana; Parsons, Jeffrey T.; Sparks, Martha A.
ABSTRACT: Despite the prominence of self-efficacy as a predictor of antiretroviral therapy (ART) adherence, relatively little work has examined domain-specific associations with steps in the care continuum or the possibility that substance use may have domain-specific associations with self-efficacy. This study analyzed data from a sample of 174 people living with HIV recruited through three clinics in the New York City metro area. Consistent with hypotheses, path analysis showed that appointments kept and viral load were each predicted only by their respective domain-specific self-efficacy components (i.e., self-efficacy for keeping appointments, B  = 0.01, p  = .04; and self-efficacy for taking ART medications, B  = −0.02, p  < .01). Path models also indicated domain-specific associations with substance use. Self-efficacy for keeping appointments was negatively associated with severity of drug use ( B  = −1.81, p  < .01); meanwhile, self-efficacy for taking ART medications was negatively associated with severity of alcohol use ( B  = −0.52, p  < .01). Accordingly, studies assessing barriers to retention in the HIV care continuum should conduct multi-domain assessments of self-efficacy for differential associations with specific behaviors. Furthermore, HIV care providers might consider screening for domain-specific self-efficacy to identify patients at risk of drop-out and tailoring interventions to various care continuum domains.